Good practices and ethical principles - Joob, Beuy; Wiwanitkit, Viroj (Revista de Gastroenterología del Perú, 2019)
We read the publication on “Good practices and ethical principles: as necessary as ever” with a great interest (1). Solari mentioned that “Frequent examples of scientific misconduct that can be found in local magazines are problems of authorship, redundant publication and plagiarism and lack of declaration of conflict of interest (1).” Indeed, the ethical problem can be detectable in both local and international publications and the problem is usually due to the unethical practitioner. It is no doubt that the recommendations and standard guidelines are useful as resources or code of conduct.